Implementación de un sistema de gestión en seguridad salud en el trabajo y medio ambiente en la organización Coninsal Ltda (2013)
This project presents a follow-up to the implementation of a system of management in safety, health in the work and environment in the company CONINSAL LTDA, organization which corporative aim is to realize the construction and/or the maintenance of the infrastructures of the companies interested by this service. The target of the project will take as a base for this implementation the guide RUC (Uniform Record of Evaluation of the safety System, safety and health in the work and Environment for Contractors), in its version 2012. To carry out this implementation the leadership and managerial commitment becomes indispensable, the development and execution of the whole personnel, the responsibility in the administration of the Risk and the evaluation and Monitoring of the same one.